Evaluation of BYTEX concentration and indoor air quality perceptions in platforms - Ya'acob, S.H.; Saidin, N.S.; Sukri, N.S.; Sahani, M. (Asian Research Publishing Network (ARPN), 2015)
Benzene, toluene, ethylbenzene and xylene (BTEX) are compounds that are harmful to health and it exists in the public transportation environment including the railway transportation. This study was conducted to determine the concentration of BTEX in the train and the platform of a railway service provider. Air sampling was conducted to compare the concentrations of BTEX in the train and platform by using activated charcoal sorbent tubes for one hour at Sentul- Klang route during peak hours. Analysis of air samples was done by using Gas Chromatography-Flame Ionization Detector (GC-FID). In addition, questionnaires were distributed to 254 respondents by cluster sampling on weekdays to examine passengers' perception on the indoor air quality (IAQ) of trains and platforms. The results indicated that 70.5% of passengers are aged 21-30 years, 11.8% aged 31-40 years, 10.6% aged 51 years and over, 5.5% aged 41-50 years and 1.6% aged 20 years and less. Majority of the passengers perceived the density of passengers on trains as dense (63.0%) and platform as less dense (49.2%). Passengers mostly feel that ventilation (57.9%), wind quality (66.9%) and IAQ (57.9%) are acceptable in the train. In the platform, passengers mostly choose an acceptable answer to the perception of ventilation (64.6%), air quality (63.0%) and IAQ (70.5%). There were no significant differences in comparison of IAQ in the train and platform by passengers' age range (p>0.05). There is a significant correlation between IAQ and passenger density, ventilation, odor and air quality in the train (p0.01). Although the overall passengers' perception of IAQ in the train and platform are acceptable, improvement is required especially regarding to indoor air quality services so that a better indoor environment can be achieved.